1996
DOI: 10.1002/(sici)1099-1379(199607)17:4<329::aid-job754>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

The interactive effects of variety, autonomy, and feedback on attitudes and performance

Abstract: SummaryJob dimensions of autonomy, variety, and feedback were objectively manipulated to evaluate their effect on perceptions of job characteristics and on job outcomes. Except for feedback level, manipulations and perceptions independently predicted satisfaction, and one significant two-way interaction emerged. In a high variety task, increased autonomy led to increased satisfaction, while in a low variety task, increased autonomy had a negligible effect on satisfaction. For performance, objective variety and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
122
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(127 citation statements)
references
References 43 publications
4
122
1
Order By: Relevance
“…Dodd and Ganster (1996) provided evidence that contextual factors such as type of supervision, type of co-workers, and satisfaction with pay, also played a moderating role on job satisfaction. However, the holistic impact of specific job characteristics on actual work behavior such as turnover, absenteeism and work effectiveness has not been fully supported in the extensive research that followed the JCM.…”
Section: Job Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dodd and Ganster (1996) provided evidence that contextual factors such as type of supervision, type of co-workers, and satisfaction with pay, also played a moderating role on job satisfaction. However, the holistic impact of specific job characteristics on actual work behavior such as turnover, absenteeism and work effectiveness has not been fully supported in the extensive research that followed the JCM.…”
Section: Job Characteristicsmentioning
confidence: 99%
“…For example, recent literature suggests that there is a need to take a holistic perspective by examining multiple variables in addition to those specified by JCM. In particular, including both individual and contextual factors is an improvement over earlier studies which have typically examined organizational outcomes such as job satisfaction from a compartmentalized perspective (Hon and Rensvold, 2006;Macky and Boxall, 2007;Wright and Geroy, 2001;Dodd and Ganster, 1996). As noted by Parker et al (2001, p. 417):…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the following characteristics have been found to relate positively to job satisfaction: autonomy and variety (Dodd & Ganster, 1996), (positive) task characteristics in general (Stepina et al, 1991), task variety (Zaffane, 1994), task clarity and significance (Ting, 1997), and task responsibilities (Blau, 1999). In the following section, some of the results of these studies are reported with respect to the relationship between task demands and job satisfaction.…”
Section: Job Satisfaction and Task Demandsmentioning
confidence: 96%
“…In a laboratory study, Dodd and Ganster (1996) examined the interactive effects of variety, and autonomy on job satisfaction. In Pearson correlations, objective task variety (r = .19), objective task autonomy (r = .30), perceived task variety (r = .48), and perceived task autonomy (.40) related positively to job satisfaction.…”
Section: Job Satisfaction and Task Demandsmentioning
confidence: 99%
See 1 more Smart Citation